Principles Of Best Interests For Children In The Broadcasting Industry - Emeralda Aisha (Publikasi Indonesia, 2023)
The regulation about child protection in the broadcasting services providers sometimes conflicts with the freedom of speech principles. Limiting children's exposure to harmful content that may affect their future is also part of the public interest principles in the communication policy. Indonesia regulates child protection in broadcasting through National Regulation (Undang-Undang) No 32 the year 2002 and there is also guidance about broadcasting behavior and broadcasting program quality. However, the regulation has several limitations, as there are several programs such as infotainment, drama, and others that do not specifically regulate children's protection. Compared to the comprehensive regulation in the United Kingdom, and specified regulation for children's classification programs In Australia, there was huge homework that Indonesia needs to catch up, on to ensure child protection is being mainstream in the broadcasting industry; especially television.